Interactions between N and C termini of α1C subunit regulate inactivation of CaV1.2 L-type Ca2+ channel. Issue 1 (2nd January 2016) - Benmocha Guggenheimer, Adva; Almagor, Lior; Tsemakhovich, Vladimir; Tripathy, Debi Ranjan; Hirsch, Joel A; Dascal, Nathan
Abstract : The modulation and regulation of voltage-gated Ca 2+ channels is affected by the pore-forming segments, the cytosolic parts of the channel, and interacting intracellular proteins. In this study we demonstrate a direct physical interaction between the N terminus (NT) and C terminus (CT) of the main subunit of the L-type Ca 2+ channel CaV 1.2, α1C, and explore the importance of this interaction for the regulation of the channel. We used biochemistry to measure the strength of the interaction and to map the location of the interaction sites, and electrophysiology to investigate the functional impact of the interaction. We show that the full-length NT (amino acids 1-154) and the proximal (close to the plasma membrane) part of the CT, pCT (amino acids 1508-1669) interact with sub-micromolar to low-micromolar affinity. Calmodulin (CaM) is not essential for the binding. The results further suggest that the NT-CT interaction regulates the channel's inactivation, and that Ca 2+, presumably through binding to calmodulin (CaM), reduces the strength of NT-CT interaction. We propose a molecular mechanism in which NT and CT of the channel serve as levers whose movements regulate inactivation by promoting changes in the transmembrane core of the channel via S1 (NT) or S6 (pCT) segments of domains I and IV, accordingly, and not as a kind of pore blocker. We hypothesize that Ca 2+ -CaM-induced changes in NT-CT interaction may, in part, underlie the acceleration of CaV 1.2 inactivation induced by Ca 2+ entry into the cell.